PEMBATALAN OLEH HAKIM TERHADAP AKTA JUAL BELI YANG DIBUAT BERDASARKAN PENIPUAN (BEDROG) - Hadi Haerul Hadi; Safiulloh Safiulloh (Res Justitia : Jurnal Ilmu Hukum, 2022)
A covenant is not always made on the basis of a free agreement but rather it is possible that there is a defect of will in the agreement. Such will defects can occur due to coercion, oversight, and fraud in making agreements. In this study, we will discuss one of the three will defects, namely fraud. The formulation of the problem to be scrutinized by the author is fraud as a reason for the cancellation of the agreement and the result of the cancellation by the judge of the Deed of Sale and Purchase made on the basis of fraud by the judge for the parties. The research method used is normative juridical research by descriptive analytical data analysis and using data collection tools, namely secondary and primary data. In this thesis, it is concluded that fraud occurs if there is a deliberate element carried out by one of the parties, namely providing untrue information or facts, and against a lie alone is not enough for the existence of fraud but there must be a series of lies that in relation to one another constitute a gimmick, and have a causal relationship if there is no fraud,   then he could not possibly close the treaty. The legal consequence arising from the Deed of Sale and Purchase annulled by the Judge is that all circumstances must be returned to their original state when there has not been a legal action in the deed in question. So that the other party in the agreement who has already received the achievements of the other party is obliged to return it. Against the Deed of Sale and Purchase which is disputed by the judge, the Land Deed Making Officer will give a note to the Minuta Deed that the deed has been annulled by the Judgment of the Court or by attaching the Judgment of the Court to the Minuta Deed concerned. Finally, for the certificate that has been reversed, one of the parties will apply for cancellation of the certificate to the National Land Agency and then by the National Land Agency will be carried out to cross out and change the name of the owner of the land rights specified in the District Court Decision on the land books, but regarding the replacement of the certificate, there are no clear provisions